Digital Twin Technology Architecture and Application for Nuclear Reactor Intelligent Operation and Maintenance - Zhuo Zhang; Jia Liu; Wei Zeng; Qingyu Huang; Xiaobo Liu (IEEE Access)
In order to improve the safety and reliability of nuclear reactors, and to enhance the digitalization and intelligence level of operation and maintenance management, a digital twin technology architecture for nuclear reactor intelligent operation and maintenance was proposed based on a conceptual analysis of nuclear reactor digital twin technology. Based on the technical implementation framework elements and their mutual relationships, the research on digital twins in nuclear reactor operation management scenarios can establish a process, and from the perspective of technical implementation, based on the number of twin intelligence operations, applications are analyzed. Digital twin has realized the organic integration of cyber space and physical space, effectively supporting nuclear reactor intelligent operations across various scenarios and achieving significant improvements in device efficiency. The research results provide certain guiding significance for the application research of nuclear reactor digital twin technology and the construction of digital twin platform for intelligent operation and maintenance.